MEMAHAMI TEKS ALQURAN DENGAN PENDEKATAN HERMENEUTIKA (Sebuah Analisis Filosofis) - Marhaban, Marhaban (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article discusses understanding the Quranic text with a hermeneutic approach to a contemporary approach that offers a new approach to interpreting the Qurâan (philosophically). In this hermeneutic approach the texts of the Quran do not stand alone, but are very dependent on the surrounding context, which includes text, context, and contextualization. The existence of hermeneutics with its own methodology brings a new nuance in the interpretation of the Quran. With this method the Qurâan is no longer considered as something sacred, because in the eyes of hermeneutics when the text descends and is in the midst of the reality of human life, it is fully owned by humans and has the right to be interpreted, internalized, and understood whatever it wants. Everything contained in the text, for hermeneutics, can be interpreted and understood its meaning clearly. And this is what distinguishes it fundamentally from the theme of interpretation in the Ulumul Quran discourse